تأثير الوسيلة التعليمية التفاعلية القائمة على الروابط التشعبية في إتقان مفردات الطلاب - Raudhatul Jannah; Muhammad Taufiq (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2025)
This study aims to analyze the effect of interactive learning media based on hyperlinks on students' vocabulary mastery. The background of this research is the low motivation and vocabulary mastery of students in Arabic language learning at MTs ABATA Al-Washliyah Islamic School in Perbaungan, which is caused by a lack of variation in learning media. This research employs a quantitative approach with a quasi-experimental design in the form of a One-Group Pretest-Posttest Design. The subjects of the study are 20 seventh-grade students from MTs ABATA Al-Washliyah Islamic School in Perbaungan. Data were collected through pretests and posttests consisting of 15 items (10 multiple-choice questions and 5 essay questions) regarding the vocabulary of al-adawatu al-madrasiyyah. Data analysis was conducted using validity and reliability tests for the instruments, Shapiro-Wilk normality test, paired sample t-test for hypothesis testing, and N-Gain test. The results indicate that the test instruments are valid and reliable, and the pretest and posttest data are normally distributed. The hypothesis test shows a significance value of 0.000 < 0.05, indicating a significant effect of interactive learning media based on hyperlinks on students' vocabulary mastery. The average pretest score was 53.00, which increased to 80.00 in the posttest. This improvement is categorized as high based on the N-Gain test with an average of 0.78. Therefore, this study concludes that interactive learning media based on hyperlinks is effective in enhancing students' vocabulary mastery.